(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
Glutaraldehyde (GTA) has been extensively used as a gelatin crosslinking agent, however, new natural ones have been suggested as more biocompatible. Polyphenols are possible candidates and the flavonols, such as rutin (RUT), also exhibit potential synergism with sunscreens and antioxidant agents used in cosmetics. In this work, gelatin microspheres (M0) were obtained and crosslinked with GTA 10 mM (MG) or RUT 10 mM (MR), dissolved in acetone:NaOH 0,01M (70:30 v/v). MG exhibited crosslinking extent of 54.4%. Gelatin, M0, MG and MR did not elicit any signs of skin damage, regarding the formation of erythema, the barrier function disruption and negative interference in the stratum corneum hydration. Oily dispersions containing M0, MG or MR, isolated or combined with benzophenone-3 or octyl methoxycinnamate, suggested that the microspheres, at a 5.0% w/w, had no additional chemical or physical photoprotective effect in vitro. Crosslinking with RUT had occurred, but in a lower degree than GTA. Microspheres had not improved sun protection parameters, although, non-treated gelatin interfered positively with the SPF for both UV filters. The in vivo studies demonstrated that these materials had very good skin compatibility.